Comparison of leachate percolation and immersion using different inoculation strategies in thermophilic solid-state anaerobic digestion of pig urine and rice straw. (April 2019) - Meng, Lingyu; Maruo, Koki; Xie, Li; Riya, Shohei; Terada, Akihiko; Hosomi, Masaaki
Highlights: Comparison of inoculation and leachate circulation methods on solid-state digestion. No difference in methane yield between complete mix and slurry application inoculation. Leachate circulation with immersion showed higher CH4 yield than percolation. CH4 yield was depended on immersion period, and 24 h showed the highest yield. Abstract: Heterogeneous distribution of substrate and microorganisms and low mass transfer limit methane production dramatically in solid-state anaerobic digestion (SS-AD). To overcome this challenge, this study determined the optimal inoculation strategy (complete premix/slurry application) for reusing solid digestate as inoculum and the optimal leachate circulation method (percolation/immersion) using batch digestion. Initially, percolation and immersion (1 h per 3 days) were compared and the result shows that immersing rice straw into leachate was superior to leachate percolation in methane production. Effect of the immersion period (24, 48 and 72 h) in each circulation cycle on methane production was then evaluated for each inoculation strategy. Methane production increased until the immersion period up to 24 h and then decreased, while the average cumulative methane yield with an immersion period of 24 h was (180 mL/g volatile solids). Slurry application with an immersion period 24 h is recommended as the optimum operating condition.